N `-[(Biphenyl-4-yl)methylene]-2-[(3,5-di-tert-butyl-4-hydroxybenzyl)s ulfanyl]acetohydrazide - Yehye, W.A.; Ariffin, A.; Rahman, N.A.; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, C(30)H(36)N(2)O(2)S, the dihedral angle between the two aromatic rings of the biphenyl residue is 31.2 (1)degrees. The two methylene C atoms subtend an angle of 99.9 (1)degrees at the S atom. In the crystal, molecules form inversion dimers linked by pairs of N-H center dot center dot center dot O hydrogen bonds. The hydroxyl group is shielded by the tert-butyl residues and is therefore not involved in any hydrogen bonding.